Adaptive control for smart-actuated base isolation structures regarding various reference-tracking strategies. (1st November 2019) - Ouyang, Yuting; Shan, Jiazeng; Shi, Weixing; Spencer, Billie F.
Highlights: The control device dynamics, CSI and model uncertainty, affect control performance. An adaptive control strategy is proposed to compensate the control device dynamics. Reference-tracking concept is integrated with backstepping control design method. The first-principle actuator model is utilized in the controller. Seismic control performance is investigated regarding various reference strategies. Abstract: An adaptive control framework considering servo-hydraulic dynamics is proposed for base isolation structures regarding various reference-tracking strategies. The reference-tracking-based adaptive controller is derived from a backstepping design methodology with Lyapunov stability analysis. Servo-hydraulic dynamics, including the control-structure interaction (CSI) and the actuator uncertainties, have significant effects on seismic control performance; accordingly, the critical issue of the control device dynamics-induced time-lag should be introduced in the control process. To drive a successful active control event, an inverse actuator model is integrated within the proposed controller. Such inverse dynamic models, with adaptive regulation characteristics, are expected to compensate the time-lag real-time. On the other hand, for a reference-tracking-based controller, control performance is determined by a reference model. Therefore, different reference generation strategies have been discussed in a comparative study by considering the effect of structure nonlinearity and substructure-interaction. To investigate the performance of the proposed controller in detail, the first example is a nonlinear single-degree-of-freedom (SDOF) system. Then, a multi-degree-of-freedom (MDOF) system with a nonlinear base isolation layer is employed in a comparative study with various reference-tracking strategies. Subsequently, the proposed control framework has been performed in a nonlinear base isolation benchmark problem; and, the control performance demonstrates the efficacy of the reference-tracking controller in a two-dimensional actuator control problem.